Invasive pulmonary aspergillosis after heart transplantation - M. A. Simonenko; M. Yu. Sitnikova; P. A. Fedotov; Yu. V. Sazonova; M. A. Bortsova; K. I. Monosova; L. A. Vasilievna; L. B. Mitrofanova; G. V. Nikolaev; M. L. Gordeev; M. A. Karpenko (Вестник трансплантологии и искусственных органов)
Objective: to assess the incidence, determine the peculiarities of the course of invasive pulmonary aspergillosis (IPA) and identify risk factors for IPA in heart transplant recipients.Materials and methods. From January 2010 to December 2019, 137 heart transplantations (HT) were performed: mean age 46 ± 14 years; male 102 (74%) and female 35 (26%). All patients received a three-component immunosuppressive therapy: calcineurin inhibitors, mycophenolate mofetil (MMF) and Glucocorticoid (GCs). Induction therapy consisted of Basiliximab (81%, n = 111) and antithymocyte immunoglobulin (15%, n = 20). A retrospective analysis of patients with identified post-HT invasive IPA was performed; risk factors for IPA were assessed. In patients with early IPA, the length of stay in the intensive care unit (ICU), the duration of mechanical ventilation, and the initial severity of the condition were studied. All patients with suspected pneumonia underwent bronchoscopy with examination of bronchoalveolar lavage (BAL) and chest computed tomography (chest CT scan).Results. During the follow-up, there were 58 episodes of pneumonia, of which 16 (28%) were IPA (age 33 to 64 years). All patients had a target level of immunosuppressive drugs concentration in blood; basiliximab was used as induction therapy in 15 of 16 patients. Half of the recipients developed IPA in the early post-HT period (less than 3 months after HT), in the rest (n = 8) – at a later date (3 months to 1 year after HT). The diagnosis was verified: 14 out of 16 patients showed an increase in the Aspergillus antigen positivity in the BAL to 7.2 (2.8 ± 1.6); chest CT scan revealed specific changes. In two patients, there were no diagnostic criteria for IPA, but the diagnosis was made based on the results of histological examination after resection of the left lower lobe of the lung. All patients received voriconazole therapy for 2 to 6 months, their immunosuppressive therapy was adjusted (tacrolimus and MMF dose adjustment) and their white blood cell count was monitored. Complete cure of the disease was achieved in 13 (81%) patients. Two patients died within 30 days after HT in the intensive care unit, one died from urogenital diseases caused by bacterial flora and leading to urosepsis, 4 months after IPA treatment was initiated. All patients had risk factors for IPA: taking immunosuppression, including GCs (n = 16), prolonged ICU stay (n = 14), inotropic support exceeding 2 days in the early post-transplant period (n = 10), cachexia during HT (n = 6), leukopenia (n = 9) and neutropenia (n = 14).Conclusion. In heart transplantat recipients, the incidence of IPA among respiratory tract infections is 28%. The risk of developing IPA was highest during the first year following HT. In the majority of recipients, the disease was detected at the early stages; diagnosis required surgical intervention in 12% of cases. A decrease in the risk of developing IPA was associated with correction of the following risk factors for this disease in all patients: volume of immunosuppressive therapy during the first year after transplantation and prevention of the development of neutropenia as a marker of infectious complications or immunosuppression overdose. Early diagnosis of IPA allowed for initiation of timely specific therapy in most recipients and achievement of a positive effect in 80% of them.